Perbankan syariah di Indonesia - Anshori, Abdul Ghofur; Indonesia (Yogyakarta : Gadjah Mada University Press, 2007)
Development of Islamic banking related to Indonesian laws and regulations
'Peraturan perundang-undangan': p. 217-218
Includes the text of: Undang-Undang Tentang Perubahan atas Undang-Undang nomor 7 tahun 1992 Tentang Perbankan.
Includes bibliographical references (p. [214]-218)
Keywords: Banking law -- Indonesia; Banks and banking -- Religious aspects -- Islam; Bank and banking -- Religious aspects